A Randomized, Placebo‐Controlled, Multiple‐Ascending‐Dose Study to Assess the Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of the Soluble Guanylate Cyclase Stimulator Praliciguat in Healthy Subjects. Issue 5 (13th November 2018) - Hanrahan, John P.; Wakefield, James D.; Wilson, Phebe J.; Mihova, Marina; Chickering, Jennifer G.; Ruff, Dennis; Hall, Michael; Milne, G. Todd; Currie, Mark G.; Profy, Albert T.
Abstract: Nitric oxide (NO)‐soluble guanylate cyclase (sGC)‐cyclic guanosine monophosphate (cGMP) signaling is central to the regulation of several physiological processes, including blood flow and inflammation. Deficient NO signaling is implicated in multiple diseases. sGC stimulators are small molecules that enhance sGC activity, particularly in combination with NO. In a randomized, placebo‐controlled phase 1 study, the safety, tolerability, pharmacokinetics, and pharmacodynamics of multiple ascending doses of the sGC stimulator praliciguat were assessed in 44 healthy adults. Four cohorts of 11 subjects (8 praliciguat, 3 placebo) received once‐daily praliciguat for 14 days before up‐titrating for 7 days (treatment sequences: 15/30 mg, 20/40 mg, 30/40 mg, and weight‐based). All doses were tolerated. No serious or severe adverse events (AEs) were reported. The most common AEs in praliciguat recipients were headache and symptoms consistent with blood pressure (BP) lowering/vasodilation. There were no laboratory, vital sign, electrocardiographic, or platelet function findings indicative of a safety concern. Pharmacokinetics were dose proportional, with an effective half‐life of 24–37 hours, supporting once‐daily dosing. Praliciguat produced dose‐related increases in plasma cGMP consistent with stimulation of sGC. Repeated once‐daily dosing showed sustained decreases in BP. Results support evaluation of praliciguat for the treatment of conditions associated with deficient NO signaling.